Physical characterization of multiparticulate systems - Michele Georges Issa; Natalia Vieira de Souza; Marcelo Dutra Duque; Humberto Gomes Ferraz (Universidade de São Paulo, 2018)
ABSTRACT The search for new pharmaceutical dosage forms and different drug delivery systems already used in therapeutics is a global trend, serving as an opportunity to expand the portfolio for the pharmaceutical industry. In this context, multiparticulate systems, such as pellets, granules, and minitablets, represent an attractive alternative, given the range of possibilities they provide. Among the methods used in the production of these systems, we highlight the process of extrusion-spheronization for pellet manufacture, wet granulation and hot-melt extrusion for the obtention of granules, and direct compression for minitablets. Although highly versatile, depending on the technology chosen, many processes and formulation variables can influence the ensuing stages of manufacture, as well as the final product. Therefore, the characterization of these small units is of fundamental importance for achieving batch homogeneity and optimal product performance. Analyses, including particle size distribution, morphology, density, porosity, mechanical strength and disintegration, are example tests used in this characterization. The objective of this review was to address the most widely used tests for the physical evaluation of multiparticulate systems.